2018
DOI: 10.1177/0739456x18787886
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Relationship between Urban Form and Excess Commuting in US Metropolitan Areas

Abstract: This article revisits the relationship between urban form and excess commuting by analyzing 206 metropolitan statistical areas in the United States. Using the most recent Census Transportation Planning Products, we revalidated the importance of using multidimensional indices when examining excess commuting across metropolitan areas. We found that higher levels of polycentricity aggravate cross-commuting, while higher central city dominance improves excess commuting. In addition, our results indicate the signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…However, there is still debate on this issue. Opponents of polycentric development argue that polycentric urban development will further exacerbate the spatial separation of jobs and residences, increase the tendency to cross-commute, and make it easier for residents to choose private cars as a mode of travel (Ha et al, 2021). Therefore, a more detailed and meticulous analysis of this issue will be an important direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still debate on this issue. Opponents of polycentric development argue that polycentric urban development will further exacerbate the spatial separation of jobs and residences, increase the tendency to cross-commute, and make it easier for residents to choose private cars as a mode of travel (Ha et al, 2021). Therefore, a more detailed and meticulous analysis of this issue will be an important direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Future work should include more elements to measure the utility of commuting. Finally, we can conduct enhanced comparative metrics, which can allow for analyses across different cities to identify global and local determinants or contributors for commuting efficiency and/or commuting equity (Ha et al., 2018; Jun et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Jun et al. (2018) and Ha et al. (2018) investigated the relationship between urban form (or spatial structure) and excess commuting in a comparative fashion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Giménez et al [61] analysed excess commuting for the self-employed versus the employed and found that employees commuted for twelve more minutes per day. Ha et al [62] utilised multi-dimensional indices to examine excess commuting pattern in 206 metropolitan areas of the United States. They revealed that a highly centralised city would reduce the excess commuting of workers.…”
Section: Excess Commutingmentioning
confidence: 99%